Can adjustment costs explain the variability and counter-cyclicality of the labour share at the firm and aggregate level? - Philip Vermeulen (European Central Bank (ECB), 2007)
This paper shows that adjustment costs modelled as firing costs of moderate size go a long way in explaining the variability and counter-cyclicality of the labour share at the firm and aggregate level. Firing costs cause firms to hire less in recessions and hire less in booms causing wage costs to fluctuate less cyclically than output, thus inducing variability and countercyclicality in the labour share. The paper develops a dynamic labour demand model with firing costs. The model is then calibrated using moments derived from 1634 French manufacturing firms and aggregate French manufacturing data. The calibrated model is able to closely match the variability and counter-cyclicality of the labour share at the firm level while it also generates a countercyclical aggregate labour share with a variability 60% of that in French aggregate manufacturing.
Keywords: D21; E25; 330; Firing Costs; labor adjustment costs; labour share; real business cycles; Kündigung; Kosten; Arbeitsnachfrage; Konjunktur; Theorie; Frankreich